Sectoral and regional expansion of emissions trading - Böhringer, Christoph; Dijkstra, Bouwe; Rosendahl, Knut Einar (Elsevier, 2014)
We consider an international emissions trading scheme with partial sectoral and regional coverage. Sectoral and regional expansion of the trading scheme is beneficial in aggregate, but not necessarily for individual countries. We simulate international CO2 emission quota markets using marginal abatement cost functions and the Copenhagen 2020 climate policy targets for selected countries that strategically allocate emissions in a bid to manipulate the quota price. Quota exporters and importers generally have conflicting interests about admitting more countries to the trading coalition, and our results indicate that some countries may lose substantially when the coalition expands in terms of new countries. For a given coalition, expanding sectoral coverage makes most countries better off, but some countries (notably the USA and Russia) may lose out due to loss of strategic advantages. In general, exporters tend to have stronger strategic power than importers.